Petri nets in ASIC design - Adamski, Marian (Zielona Góra: Uniwersytet Zielonogórski)
This paper shows how Petri nets can be used for the design of a complex digital system. Many well known methods for the system description such as flowchart (ASM-charts) are not suitable for the description of parallel processes. Petri nets provide a mechanism which is well suited for representing such important phenomena in digital systems as parallelism and hierarchism.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka